Tablet formulation development focusing on the functional behaviour of water uptake and swelling - Jan Lenz (Elsevier, 2021)
The functional behaviour of tablets is strongly influenced by their manufacturing process and the choice of excipients. Water uptake and swelling are prerequisites for tablet disintegration, dispersion and hence active pharmaceutical ingredient (API) dissolution. High proportions of polymeric excipients in tablets, which are typically used as API carriers in amorphous solid dispersions (ASDs), may be challenging due to the formation of a gelling polymer network (GPN). In this study, systematic investigations into the formulation development of tablets containing polymeric and other excipients are performed by water uptake and swelling analysis. The impact of tablet composition and porosity as well as pH of the test medium are investigated. The pH affects the analysis results for Eudragit L100–55 and Eudragit EPO. HPMC and Kollidon VA64 inhibit water uptake and swelling of tablets due to the formation of a GPN. High tablet porosity, coarse particle size of the polymer and the addition of fillers and disintegrants can reduce the negative impact of a GPN on tablet performance. The application of lubricants slows down the analysed processes. Water uptake and swelling data are fitted to an empirical model obtaining four characteristic parameters to facilitate the simple quantitative assessment of varying tablet formulations and structural properties.